The association of suicide risk with negative life events and social support according to gender in Asian patients with major depressive disorder - Subin Park (2018)
© 2015 Elsevier Ireland Ltd. We investigated the associations between negative life events, social support, depressive and hostile symptoms, and suicide risk according to gender in multinational Asian patients with major depressive disorder (MDD). A total of 547 outpatients with MDD (352 women and 195 men, mean age of 39.58 ± 13.21 years) were recruited in China, South Korea, Malaysia, Singapore, Thailand, and Taiwan. All patients were assessed with the Mini-International Neuropsychiatric Interview, the Montgomery-Asberg Depression Rating Scale, the Symptoms Checklist 90-Revised, the Multidimensional Scale of Perceived Social Support, and the List of Threatening Experiences. Negative life events, social support, depressive symptoms, and hostility were all significantly associated with suicidality in female MDD patients. However, only depressive symptoms and hostility were significantly associated with suicidality in male patients. Depression severity and hostility only partially mediated the association of negative life events and poor social support with suicidality in female patients. In contrast, hostility fully mediated the association of negative life events and poor social support with suicidality in male patients. Our results highlight the need of in-depth assessment of suicide risk for depressed female patients who report a number of negative life events and poor social supports, even if they do not show severe psychopathology.